The relationship between family attitudes and roles with leprosy patients' self-care at the Jongaya Health Center in Makassar City - Khaeriah, Misbah; Hamzah, Hamsiah; Nofianti, Nofianti (Omni Health Journal, 2024)
Background: Leprosy or also called Morbus Hansen is a chronic infectious disease caused by Mycobacterium Leprae. This is influenced by several factors, one of which is the attitude and role of the family to the availability of resources that can affect respondents' self-care. Objective: This study aims to determine the attitudes and roles of families with leprosy patients' self-care at the Jongaya Health Center in Makassar City. Methods: This type of research is an analytical survey with a Cross Sectional Study approach, sampling is carried out by the Total sampling method of 32 respondents. Results: Based on the results of the Chi-Square test, there was a relationship between attitude and self-care (p = 0.002 where p = α 0.05) and there was a relationship between family roles and leprosy patient self-care (p = 0.000 where p = α 0.05) Conclusion: Based on the results of this study, it can be concluded that there is a significant relationship between family attitudes and roles with the self-care behavior of leprosy patients at the Jongaya Health Center in Makassar City. Strengthening family support and active roles is essential to improve self-care among leprosy patients and reduce the risk of further disability.